Web-Based Extracurricular Activity Management Information System (Case Study: SMA Negeri 1 Mande) - Fietri Setiawati Sulaeman; Siti Nazilah; Mohamad Kany Legiawan; Nabillah Fira Yamin Hasibuan (Media Jurnal Informatika, 2025)
The advancement of information technology continues to grow in line with increasing societal needs, particularly in the era of globalization. Various sectors such as transportation, communication, healthcare, and education demonstrate that technology has become an essential part of daily life. One significant application of this technology is the use of web-based information systems, which can enhance data processing speed, support decision-making, and save both time and cost. SMA Negeri 1 Mande, located in Mande District, Cianjur Regency, still manages extracurricular activities manually. This has led to various problems, including errors in recording new member data, activity scheduling, attendance tracking, achievement documentation, submission of permission letters, and funding requests. In addition, data retrieval is often difficult due to damaged or disorganized documents. Competition announcements are still delivered verbally, and communication between students and extracurricular advisors is not optimally facilitated. This study aims to develop a Web-Based Extracurricular Activity Management Information System using the PHP programming language and the Laravel framework. The system is designed to automate processes such as member registration, data management, activity scheduling, attendance recording and reporting, and online submission of letters. Communication features such as live chat and discussion forums are also provided to support interaction between supervisors and members. The results of this study produced an information system that improves the efficiency and effectiveness of extracurricular activity management and can be integrated with the school’s operational needs. Based on the testing results, the system accelerated the registration process by up to 60% and attendance recording by 50% compared to manual methods.